Biology and management of rice insects (Wiley, 1994)
This book fills the need for a comprehensive treatment of rice entomology under one cover. The contributors to this book, drawn from various related disciplines, discuss the fundamentals of rice entomology, the biology and ecology of rice insects and the various techniques of rice insect control , namely, host plant resistance, cultural, mechanical and physical controls, predators and parasitoids, pathogens and insecticides (Publisher description)